TAMBO: Searching for tau neutrinos in the Peruvian Andes - William G. Thompson, on behalf of the TAMBO collaboration. (SciPost Physics Proceedings, 2025)
TAMBO is a planned next-generation neutrino observatory sensitive to 1-100 PeV Earth-skimming tau neutrinos. This tau neutrino specificity will provide a high-purity sample of astrophysical neutrinos whose locations on the sky can then be used to improve the sensitivities of all-flavor neutrino observatories. The observatory will be located in a deep canyon and will comprise an array of water-Cherenkov and plastic scintillator air-shower detectors. In this proceeding, I will summarize the current status of the updated TAMBO simulation package, which is currently being used for detector optimization and reconstruction studies.